Pengaruh Pemasaran Digital dan Kemudahan Penggunaan Platform Marketplace Shopee terhadap Minat Beli Mahasiswa Bisnis Digital - Afifah, Haya; Jasmien, Laila; Qisthi, Miizan; Ihsan, Raka; Syti Sarah Maesaroh (STEKOM PRESS, 2023)
This study aims to analyze the effect of digital marketing and the ease of use of the Shopee marketplace platform on the buying interest of digital business students. In an increasingly advanced digital era, digital marketing and the use of marketplace platforms have become important factors in influencing consumer behavior, including students. This research involved digital business student respondents who actively use the Shopee marketplace platform. The data collection method was carried out through an online survey using a structured questionnaire. Digital marketing variables and platform ease of use are measured using a Likert scale. The collected data were then analyzed using regression analysis techniques. The findings of this study indicate that digital marketing significantly and profitably influences the purchase intention of students studying digital business. Student buying interest can be increased using efficient digital marketing techniques including social media, online advertising and related content. In addition, research findings show that student buying interest is positively and significantly influenced by the ease of use of the Shopee marketplace platform. Students are more likely to be interested and interested in transacting through platforms that are easy to use, have intuitive navigation and easy payment procedures. In conclusion, digital marketing and the ease of use of the Shopee marketplace platform have had a major impact on the buying interest of students studying digital business. The results of this study provide a better understanding of the factors that influence student buying behavior in the context of digital business. These findings can serve as guidelines for companies or online sellers in designing effective marketing strategies and improving the user experience on the marketplace platform. Keywords: digital marketing, ease of use, purchase intention.